THU0002 Novel pathogenic stop codon mutation in the nf-Κb p65 subunit (RELA) associated with both behÇet's disease like syndrome and neuromyelitis optica in an irish family. (12th June 2018) - Adeeb, F.; Dorris, E.R.; Tariq, S.; Ng, W.L.; Stack, A.G.; Wilson, A.G.; Fraser, A.D.
Abstract : Background: Behçet's disease (BD) has a complex multifactorial pathogenesis and presents with phenotypic heterogeneity predominantly mucocutaneous ulcerations, ocular lesions and skin manifestations. More recently, there have been reported cases of monogenic spectrum defects presented with BD-like similarities or phenotype. Objectives: We investigated an Irish Caucasian family of eleven that included two half-sisters with early-onset BD, and another sister with neuromyelitis optica, all who were born to asymptomatic non-consanguines parents. More recently, one of the sisters' daughter developed recurrent oral aphthosis at the age of 10 years old. Methods: Peripheral blood mononuclear cells were extracted from patients and non-affected donor blood using standard fractionation methods. Following quality assessment and quantification whole exome sequencing was performed on all participants. Results: Whole exome sequencing data identified segregation of a novel pathogenic stop codon mutation in the nuclear factor NF-κB p65 subunit (RelA) resulting in a non-functional protein. The mutation involves cytosine deletion and results in a His487ThrfsTer7 frameshift (His487ThrfsTer7) RelA resulting in loss of transcription activation-1 (TA1) and a portion of TA2 from RelA. The mutation was seen within the three generations, including the three half-sisters, their father as well as one of the proband's daughter, potentially describing a new syndrome. Conclusions: Our study suggests that loss-of-function mutations in the NF-κB pathway, a pivotal mediator of inflammation and apoptosis, are linked with the development of familial early-onset BD-like syndromes. Better insights and further understanding of this "orphan" immunogenetic syndrome carries high clinical impact to assist early disease recognition and potential discoveries of novel targeted therapies. Disclosure of Interest: None declared